Право вільної елекції полковника Війська Запорозького: козацькі традиції у випробуванні імперськими новаціями - Горобець, В.М. (Український історичний журнал, 2015)
Досліджується вплив російської влади на трансформацію однієї з наріжних засад культури козацької військової демократії середини XVIІ – першої половини XVIІІ ст. – права вільної елекції старшини, зокрема полковників Війська Запорозького. Визначено правові акти та політичні заборони російської влади, через які здійснювалися обмеження, з’ясовано, наскільки ефективними ці заборони були на практиці та яким чином втручання ззовні вплинуло на іманентні процеси розвитку козацької державності. In this article researches the influence of Russian powers on the transformation of one of the foundation bases of culture of Cossack military democracy of the middle 17th – first half of 18th centuries. It is talked of the right to free elections of the foreman, in particular the colonels of the Zaporozhian Army. Author determines the legal acts and political interdictions of Russian powers. Through them were implemented the limitations. Also was found how effective were these prohibitions in practice and how it affected to the immanent processes of the development of the Cossack state.